Latex beads internalization and quantitative proteomics join forces to decipher the endosomal proteome. (June 2011) - Guimarães de Araújo, Mariana Eça; Huber, Lukas Alfons; Stasyk, Taras
Evaluation of: Duclos S, Clavarino G, Rousserie G et al. The endosomal proteome of macrophage and dendritic cells. Proteomics 11(5), 854–864 (2011). The proteome analysis of endocytic compartments has been constrained by the limited purity of the organelle fractions obtained by current biochemical methods. Duclos and coworkers have developed a novel method to isolate highly purified endosomal organelles based on small latex beads internalization followed by gradient centrifugation and successfully combined it with a redundant peptide counting method to compare the relative abundance of proteins in organelles. The presence of bona fide markers in their respective subcellular organelles and the identification of several new endosomal-associated proteins, attested the applicability of their combinatory approach. Future applications of this strategy may deliver a comprehensive endosomal proteome chart: from the identification of the key players to the determination of time and signaling-dependent proteome changes. As a long-term perspective, such an approach may unveil new clues to the molecular mechanisms underlining human diseases associated with endosomal biogenesis defects.